Caste and class : The formation of a mestizo and mercantile peasantry in the Cochabamba region - Larson, Brooke (1990)
In 1985, Tulio Halperín Donghi wrote an impressive summary of the latest achievements in the field of Latin American historiography. He highlighted the growing diversity of themes, methodologies, and interpretations that have been developed for a variety of regions and historical periods. Above all, he emphasized that enigmatic centuries such as those of the XVII and XIX, have been clarified. In addition, the historical work is increasingly enriched by the contributions of other disciplines such as anthropology, political science, and economics.